Autoavaliação estratégica: contribuições para o Mestrado Profissional e Interdisciplinar em Prestação Jurisdicional e Direitos Humanos - Melo, Marcela Santa Cruz (Universidade Federal do Tocantins, 2022)
This study is a technical report that presents a strategic model of self-evaluation to support the postgraduate stricto sensu professional and interdisciplinary Master's Degree in Jurisdictional Provision and Human Rights (PPGPJDH), from the Federal University of Tocantins (UFT) in partnership with the Escola Superior da Magistratura Tocantinense (Esmat). The guiding question of this research was how to implement a self-assessment model in the PPGPJDH that meets the requirements of CAPES and at the same time contemplates the professional and interdisciplinary aspects from the technical-intellectual products generated and that these reverberate in a systemic way in the social-academic field of the Tocantins surroundings and the Legal Amazon. Among the objectives, it was sought, in general, to establish a self- assessment system in the PPGPJDH to glimpse and understand the perception of benefit of the technical product produced by the graduate and its impact on society. As for the specifics, we have: analyzing the potential for transferring the results of the intellectual production of the work-products produced in classes 1 to 6, with a view to generating changes for society regarding the specific objectives in said program and examining the speech of graduates, via online questionnaire; form the Self-Assessment Committee (CAA) to collaborate in the awareness-raising process and continue the self-reflection process, with the development of the management process (technical product); generate elements to measure the academic- social impact obtained in terms of the work and academic trajectories projected, materializing the movement of real or realized impact and the potential in the jurisdictional provision and in Human Rights. Therefore, as a methodological approach, the participant research was used with the analysis of the works deposited by graduates of classes 1 to 6 of the PPGPJDH in the UFT's Institutional Repository, carrying out activities aimed at technical production, namely: social technology, professional training course, organized event, conclusive technical report – elaborate management tool, manual, presentation of work, product development, bibliographic production and also the application of a self-assessment questionnaire to the same public. The results indicated that 80.2% of the graduates continue to work in the same place since they attended the PPGPJDH; that there is a predominance of the Law course in terms of graduation; 68.1% of graduates are interested in participating in extension activities; 67% consider that their final course work had a potential impact (not implemented); and also that 67% saw the TJTO as the institution benefiting from the work.